Analyzing Customer Loyalty of ShopeePay in Restaurant Industry at Manado - Brigitta Febiola Saniska Magdalena Atotoy; Paulus Kindangen; Regina Trifena Saerang (Universitas Sam Ratulangi, 2022)
The purpose of this research is to analyzing customer loyalty of shopeepay in restaurant industry at manado,. 100 samples were collected with questionnaire distributed to the respondent who have experience using digital payment platform especially shopeepay. this research used quantitative method Data analysis used Multiple Linear Regression analysis method conducted by using SPSS 25 version software. The result of this research shows that performance expectation, effort expectation, social influence, facilitating condition, hedonic motivation, price value, and habit have a positive and significant influence to customer loyalty of shopeepay in restaurant industry at Manado and 6 points likert scale was used to help the data analysis in this research for analyzing customer loyalty.